Strategy for Forming Students Religious Attitudes - Fuad Fuad; Almwalla Mona (IJCRE - International Journal of Culture, Religion, and Education, 2025)
This research is motivated by deviant behavior among teenagers, one of which is the moral crisis problem of students in school. The era of rapid and free globalization can damage students faith, worship and morals if they do not get guidance or direction from parents and teachers, as well as the school in shaping students religious attitudes. The purpose of the research to know the strategy for forming students creeds and student worship through the madrasah diniyah program, and the strategy for the formation of student morals through the diniyah madrasa program. The research method in this thesis uses a qualitative phenomenological approach, a type of field research, and a multi-site. Research data sources consist of informants, events, locations, and documents, data collection techniques with participant observation, in-depth interviews and documentation. The results of the research: Strategies for the Formation of Students Religious Attitudes Through the Diniyah Madrasah Program (MADIN) is Aqidah values with the story method, translating asmaul husna, and Understanding the obligatory nature of God worship: Islamic Shari’a values, accustom congregational prayers, familiarize mahdhah worship and ghoiru mahdhah. Morals values through the study of the matlab book religious and reflecting the student’s morals.